Chrysopogon densipaniculatus (Poaceae: Andropogoneae): a new species from India - Tiwari, Arjun Prasad; Landge, Shahid Nawaz (Phytotaxa, 2022)
Chrysopogon densipaniculatus, a remarkable new species has been described and illustrated from Korba district of Chhattisgarh, India. The species is allied to C. serrulatus but may be distinguished by the dense panicle inflorescence, glandular peduncle, upper lemma and palea of the pedicelled spikelet bi-dentate to tridentate, the latter of which is reduced a minute scale. Detailed morphological description, distribution, habitat and ecology, illustration of floral parts and colour photographs, IUCN conservation status and relevant taxonomic notes of the species are provided. A key for the identification of Chrysopogon species in India is also given to facilitate the proper identification.